Assessment and Prognostic Resources for Gross Motor Development in a Child with Cerebral Palsy Related to Congenital Zika Syndrome - Ventura, Paloma A.; Carvalho, Alessandra L. de; Nascimento-Carvalho, Cristiana M. (Neuropediatrics, 2024)
This article describes how the Gross Motor Ability Estimator (GMAE) software can provide important information based on the Gross Motor Function Measure (GMFM)-66 score of a child with congenital Zika syndrome.A child was assessed at 9, 17, and 25 months of age through the GMFM-66. At 2 years, the child's gross motor ability was estimated and classified according to the Gross Motor Function Classification System (GMFCS).At 2 years of age, the child in this case required assistance to roll and was unable to maintain antigravity trunk posture in sitting position, typical abilities of GMFCS level V.GMAE can be useful to guide health professionals that care for children with lifelong physical and developmental care needs. This is the first study that demonstrated how to use the GMAE in this specific population.
Keywords: Gross Motor Ability Estimator; Gross Motor Function Measure; item map by difficulty order; congenital Zika syndrome; cerebral palsy; motor prognosis